Acoustic Processing of Fluidic Samples for Planetary Exploration - Sherrit, Stewart; Badescu, Mircea; Noell, Aaron C.; Kehl, Florian; Mora, Maria F.; Oborny, Nathan J.; Creamer, Jessica S.; Willis, Peter A. (Frontiers in Space Technologies, 2022)
This paper discusses a class of compact sample processing instrumentation using solid-state mechanisms that use acoustic waves to process samples prior to delivery to an in-situ instrument. Some of the acoustic sample processes that can be used to aid in preparation of liquid and liquid/solid mixtures include: mixing, milling, cavitating, lysing, heating, streaming, stirring, lofting, concentrating, segregating, and filtering. We will review these acoustic processes and show how they are generated using electromechanical systems. In addition to processing, these transduction systems could also use acoustics to interrogate physical properties such as the state of the sample, the acoustic velocity, and its attenuation. In order to generate these processes and sensing capabilities at these frequencies, a transduction mechanism is required to produce stress waves from electrical signals and vice versa. One commonly used technique is to use piezoelectric transducers that generate a stress that is linearly proportional to the voltage across the transducer and a voltage that is proportional to the stress on a transducer’s face. A variety of transducer modes are available to excite the sample, including thickness, transverse, radial, and shear extensional, and these can be used to build composite resonance structures including ultrasonic horns, tuning forks, bimorph, and unimorph benders to increase stress generated in the sample. We discuss how to model the acoustic interactions with the sample and the sample chamber in order to produce the required stress waves and illustrate the use of network models of piezoelectric transducers to accomplish this modeling. We demonstrate how to build up these models using Mason’s equivalent circuit for a piezoelectric and network models for acoustic layers in a design. Finally, to illustrate this acoustic processing ability, we will discuss a few systems that we have developed for sample handling systems for other planetary bodies like Mars and ocean worlds Enceladus and Europa.